tert-Butyl nitrite induced radical dimerization of primary thioamides and selenoamides at room temperature - Chauhan, Swati; Chaudhary, Priyanka; Singh, Adesh Kumar; Verma, Pratibha; Srivastava, Vandana; Kandasamy, Jeyakumar (Tetrahedron letters, 2018)
[Display omitted] •Dimerization of thioamides and seleoamides was achieved with tert-butyl nitrite.•Reaction proceeds under catalyst and metal free conditions at room temperature.•Reaction proceeds through radical mechanism.•Easy operation, broad substrate scope and efficient conversion are the advantages. A simple and efficient method for the dimerization of primary thioamides into 1,2,4-thiadiazoles using tert-butyl nitrite is described. The optimized condition was also found to be suitable for the dimerization of benzoselenoamides into 1,2,4-selenadiazoles. All the reactions proceed smoothly at room temperature and gave the desired products in excellent yields in a short span of time.